Essays on structural microeconometrics: Perturbed utility and equilibrium models - Esben Scriver Andersen (University of Copenhagen, Department of Economics, 2022)
his thesis consists of three independent chapters. Each chapter analyzes the equilibrium outcomes of the labor and housing market by describing the behavior of the participants in the markets by the perturbed utility model. This class of models allows for a more general substitution patterns as opposed to the mostly used model class in the literature, the additive random utility model. Substitution patterns is important, as wages and housing prices not only reflect the productivity of labor and the quality of the properties, but also reflect the availability of close substitutes. The first chapter Multidimensional matching and labor market complementarity is written in cooperation with Young Jun Lee. We propose an empirical framework for matching in a frictionless labor market, where workers and firms negotiate over wages and other contractual terms (e.g. whether to work part time or full time). The behavior of workers and firms is described by a class of static perturbed utility models in which alternatives may be complements or substitutes. We show that a unique equilibrium exists and how the equilibrium of the model is obtained. As a proof of concept, we estimate the model based on aggregated data for the Danish labor market and find that workers with different educational levels can be complements in production, which the additive random utility model rules out. [...]
Keywords: 330; Mikroökonometrie; Theorie